Physical Health, Media Use, and Mental Health in Children and Adolescents With ADHD During the COVID-19 Pandemic in Australia. Issue 4 (February 2022) - Sciberras, Emma; Patel, Pooja; Stokes, Mark A.; Coghill, David; Middeldorp, Christel M.; Bellgrove, Mark A.; Becker, Stephen P.; Efron, Daryl; Stringaris, Argyris; Faraone, Stephen V.; Bellows, Susannah T.; Quach, Jon; et al.
Objective: To examine the impact of COVID-19 restrictions among children with attention-deficit/hyperactivity disorder (ADHD). Methods: Parents of 213 Australian children (5–17 years) with ADHD completed a survey in May 2020 when COVID-19 restrictions were in place (i.e., requiring citizens to stay at home except for essential reasons). Results: Compared to pre-pandemic, children had less exercise (Odds Ratio (OR) = 0.4; 95% CI 0.3–0.6), less outdoor time (OR = 0.4; 95% 0.3–0.6), and less enjoyment in activities (OR = 6.5; 95% CI 4.0–10.4), while television (OR = 4.0; 95% CI 2.5–6.5), social media (OR = 2.4; 95% CI 1.3–4.5), gaming (OR = 2.0; 95% CI 1.3–3.0), sad/depressed mood (OR = 1.8; 95% CI 1.2–2.8), and loneliness (OR = 3.6; 95% CI 2.3–5.5) were increased. Child stress about COVID-19 restrictions was associated with poorer functioning across most domains. Most parents (64%) reported positive changes for their child including more family time. Conclusions: COVID-19 restrictions were associated with both negative and positive impacts among children with ADHD.